Manajemen Pelayanan Penumpang Di Terminal Bus - M, Ariyanto; Zulkifli, Zulkifli; Darmawanto, Darmawanto; Hamirul, Hamirul; Tarjo, Tarjo (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2022)
This paper is to find out the use of bus terminals in serving passengers by using a descriptive method with a qualitative approach and using data collection techniques with interviews, 13 informants with research results Bus terminal utilization of passenger services namely Determining Terminal Locations, arranging terminal supporting facilities, Flow arrangement traffic in the terminal supervision area, scheduling of officers in the terminal and evaluation of the terminal operating system. Obstacles encountered in passenger service to the effectiveness of using bus terminals include traffic facilities and infrastructure are still limited, traffic management has not functioned optimally, passenger public transport services are inadequate. Efforts carried out in the service effectiveness of bus terminal utilization on passenger services, namely Improving the waiting area service and the flow of public vehicles within the terminal, improving service in the arrival and departure of vehicles according to a predetermined schedule, Collecting passenger terminal services and Increasing the current flow settings crossing in the terminal surveillance area